Athletic apparel licensing arrangements - Tale, Nina J.; Elumba, Ma. Patricia S. (2001.)
This study is an attempt to develop an descriptive profile of the prevailing licensing arrangements of some of the top athletic apparel licenses in the Philippines. The specifics of the licensing arrangements of the respondent companies were obtained through survey questionnaires and interviews. The information gathered were also identified based on the Intellectual Property Regulations on Licensing. The existing situation of those included in this study revealed that their reltionship with their licensors are somewhat open and restrictive. Listed below are some of the findings of the study: a) Both respondents were granted exclusive rights to manufacture and distribute the licensed products; b) Both respondents receive advertising and promotion assistance from their Licensor; c) Respondent "B"s licensor provides more technical assistance than Respondent "A"s Licensor; d) Respondent "B" is required by its Licensor to purchase materials only from the Licensor or Licensor nominated firms; e) Respondent "A" is not required to purchase materials from specific firms of from the Licensor itself; f) Both of the respondents' Licensors have inhibited themselves from the liabilities that may arise from the licensee's negligence; g) Both the respondents are not required to keep information obtained from the Technology Transfer Agreement confidential, beyond a reasonable period of time; h) Respondent "B"s Licensor has agreed to provide training to employees upon the request of the respondent; i) Both Licensors have also agreed to continuously update and make available all new products and technology that would be useful to the operation of the Business. From the gathered information, it become apparent that the vantage point of Licensing is not only its profitability but the access to marketing support and technical assistance as well. And although some government regulations on licensing may often discourage technology transfers from foreign source, a well negotiated and carefully drafted licensing arrangement could be mutually beneficial to both the Licensor and Licensee.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: License agreements--Philippines.